Comparison of prime editing and base editing for generating the novel WRN R732P mutation in breast cancer cells - Nikku, Laura (My University, 2023)
Breast cancer is the most common cancer among women in Finland and worldwide, but, fortunately, the survival rate in Finland is over 90 %. Genome instability and mutations are one reason for the formation of cancer. WRN is one of the five RecQ helicases and has an important role in maintaining genome stability. Prime editing and base editing are CRISPR-Cas9 genome editing methods that do not require double-strand breaks or donor DNA. Prime editing requires a prime editor (PE) composed of a catalytically impaired Cas9 endonuclease linked to reverse transcriptase and green fluorescent protein (GFP). The PE is directed to the desired editing site by engineered prime editing guide RNA (epegRNA), which also carries the template with the desired edit. Base editing requires a base editor (BE) and a guide RNA (gRNA) for guiding the BE to the correct site. The aim of the thesis was to generate the novel WRN R732P mutation into breast cancer cells using prime editing and base editing and compare which of the methods gives the highest editing efficiency. Three different primer binding site (PBS) lengths and reverse transcriptase template (RTT) lengths were tested to determine the optimal PBS and RTT lengths for this specific locus. Two gRNAs were used to direct a nick to the non-edited strand in the prime editing constructs to favor the edited strand as a template. CAL-51 cells were transfected with the prime editor, epegRNA, gRNA, and hMLH1dn for prime editing, and CGBE1 base editor and CGBE gRNA for base editing, and GFP-positive cells were sorted. Editing efficiency was measured with droplet digital PCR assay to determine the fractional abundance of the mutant allele versus the wild type allele. Both gRNAs in prime editing worked but nicking further away from the edit site overall worked better. Editing efficiency was at its highest at 36,9 ± 6,2 % with PBS of 10 nucleotides (nt) and RTT of 22 nt. The trends for prime editing were clear: the longer the epegRNA, the worse the editing efficiency. Base editing had a 5,7 ± 4,6 % editing efficiency proposing that the first version of the C-to-G base editor still needs optimizing. In conclusion, base editing can be used to generate the WRN R732P mutation but optimizing the PBS and RTT lengths for the specific locus is beneficial to obtain the optimal editing efficiency.
Keywords: breast cancer, WRN, prime editing, base editing